2021
DOI: 10.3390/ijms22136770
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-miRNA-lncRNA Regulatory Network in Nonalcoholic Fatty Liver Disease

Abstract: Aim: we aimed to construct a bioinformatics-based co-regulatory network of mRNAs and non coding RNAs (ncRNAs), which is implicated in the pathogenesis of non-alcoholic fatty liver disease (NAFLD), followed by its validation in a NAFLD animal model. Materials and Methods: The mRNAs–miRNAs–lncRNAs regulatory network involved in NAFLD was retrieved and constructed utilizing bioinformatics tools. Then, we validated this network using an NAFLD animal model, high sucrose and high fat diet (HSHF)-fed rats. Finally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 83 publications
0
16
0
Order By: Relevance
“…The liver is considered an organ of the innate immune response that filter endogenous signaling molecules and invading pathogens. Accordingly, the presence of multiple insults concomitantly activates the components of innate immunity, thus triggering chronic hepatic inflammation and steatosis, allowing the progression of NAFLD into NASH [ 26 ]. Similarly, NOD-like receptors (NLRs) had been recognized as an important aspect in NASH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is considered an organ of the innate immune response that filter endogenous signaling molecules and invading pathogens. Accordingly, the presence of multiple insults concomitantly activates the components of innate immunity, thus triggering chronic hepatic inflammation and steatosis, allowing the progression of NAFLD into NASH [ 26 ]. Similarly, NOD-like receptors (NLRs) had been recognized as an important aspect in NASH pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Long intervening non-coding RNA (lincRNA) is a subclass of non-coding RNA ( 37 ). OLMALINC (LINC00263) and RPARP-AS1 have been identified as important regulators of the pathogenesis of non-alcoholic fatty liver disease ( 38 , 39 ). Studies have shown that OLMALINC (LINC00263), regulated by heterogeneous nuclear ribonucleoprotein K, upregulates CAPN2 through miR-147a, and thus plays an important role in cancer and malignant tumors ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has also highlighted the implicating role of epigenetic mechanisms, including noncoding RNAs (ncRNAs), in the pathogenesis of human NASH [ 10 ]. The main ncRNA classes, long ncRNAs (lncRNAs) and micro RNAs (miRNAs) translate alterations in metabolism and nutrients into a heritable pattern of gene expression [ 11 ]. Moreover, these ncRNAs are playing pivotal roles in inflammation, insulin signaling, and metabolism [ 12 , 13 ] and may facilitate the identification of non-invasive biomarkers or the development of therapeutic strategies for NASH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these ncRNAs are playing pivotal roles in inflammation, insulin signaling, and metabolism [ 12 , 13 ] and may facilitate the identification of non-invasive biomarkers or the development of therapeutic strategies for NASH [ 10 ]. Clearly, emerging data also demonstrates the critical role of bioinformatic analysis to identify candidate RNA species as biomarkers for NASH screening, diagnosis, and therapy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%